Electropolymerized o‐Phenylenediamine on Graphite Promoting the Electrochemical Detection of Nafcillin. Issue 1 (26th August 2019) - Bottari, Fabio; Moro, Giulia; Sleegers, Nick; Florea, Anca; Cowen, Todd; Piletsky, Sergey; van Nuijs, Alexander L. N.; De Wael, Karolien
Abstract: By combining molecular modelling and electrochemistry we envision the creation of modified electrodes tailored for a more sensitive and selective detection of a single analyte. In this study we report on a graphite screen printed electrode modified with electropolymerized o‐phenylenediamine, selected by rational design, which promotes the detection of nafcillin (NAF), an antibiotic. Parameters such as monomer concentration, pH and number of electropolymerization cycles were optimized to obtain the highest current signal for the target upon amperometric detection. NAF identification was based on the redox process at +1.1 V (vs pseudo Ag), ascribed to the oxidation of the C‐7 side chain. With the optimized modification protocol, a two‐fold increase in nafcillin signal could be obtained: the calibration plot in 0.1 M Britton‐Robinson buffer pH 4 showed a limit of detection of 80 nM with improved sensitivity and reproducibility (RSD<5 %) compared to the detection at non‐modified electrodes. Abstract :